Impact of CYP2B6 genotype, tuberculosis therapy, and formulation on efavirenz pharmacokinetics in infants and children under 40 months of age. (15th March 2022) - Nikanjam, Mina; Tran, Lana; Chadwick, Ellen G.; Bwakura-Dangarembizi, Mutsa; Bolton Moore, Carolyn; Samson, Pearl; Spector, Stephen A.; Chakhtoura, Nahida; Jean-Philippe, Patrick; Frenkel, Lisa; Zimmer, Bonnie; Benns, Alex; et al.
Abstract : Objective: Dosing efavirenz (EFV) in children less than 3 years of age is challenging due to large variability in drug levels. This study evaluated differences in pharmacokinetics with tuberculosis (TB) therapy, formulation, age, and CYP2B6 genotype. Design: Pharmacokinetic data from three IMPAACT/PACTG studies (P382, P1021, and P1070) for children initiating therapy less than 40 months of age were evaluated. Methods: Pharmacokinetic data were combined in a population pharmacokinetic model. Exposure from the 2-week pharmacokinetic visit was compared with changes in viral RNA between the Week 0 and Week 4 visits. Results: The model included 103 participants (19 on TB therapy). CYP2B6 516 genotype information was available for 82 participants (TT: 15, GT: 28, GG: 39). Median age at the first pharmacokinetic visit was 17.0 months (range: 2.0–39.0 months). Liquid formulation led to a 42% decrease in bioavailability compared with opened capsules. TB therapy (isoniazid and rifampin) led to a 29% decreased clearance, however Monte Carlo simulations demonstrated the majority of participants on TB therapy receiving standard EFV dosing to be in the target area under the curve range. Clearance was 5.3-fold higher for GG than TT genotype and 3.3-fold higher for GT than TT genotype. Age did not have a significant effect on clearance in the final model. Initial viral RNA decay was lower for patients in the lowest quartile of exposures (area under the curves) than for higher quartiles ( P  = 0.013). Conclusion: EFV dosing should account for CYP2B6 516 genotype and formulation, but does not require adjustment for concurrent TB therapy.